EKSISTENSI NASKAH LONTAR MASYARAKAT BALI (STUDI KASUS HASIL PEMETAAN PENUYULUH BAHASA BALI TAHUN 2016-2018) - Ardiyasa, I Nyoman Suka (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2021)
The lontar manuscripts are written using Balinese script, the contents in the lontar manuscripts are various such as literature in the form of satua, geguritan, babad, usada, bebantenan, asta kosala kosali and others. Balinese literature written on lontar is one of the cultural heritages that is still being inherited today. From the findings, most of them are in an unkempt condition, this is due to the lack of public knowledge in caring for their lontar manuscripts. In general, the lontar manuscripts found in the community can be classified in the form of speech, kanda, wariga and usada, geguritan, weda, babad, kakawin texts in the form of lontar and other lontars which have their own peculiarities. From the results of the mapping carried out by Balinese Language Instructors from 2016, 2017, 2018, there were 25,106 Cakep Lontar spreads in 9 (nine) districts / cities in Bali. Meanwhile, the people who have the most lontar collections are in Gianyar Regency, while the smallest is in Jembrana Regency. This data shows that the existence of lontar manuscripts in the community is still very much found, even though some of the owners do not fully understand the contents of the lontar in their possession. With the existence of Balinese language instructors, it is hoped that the community will have more knowledge about lontar manuscripts and the growing awareness of the Balinese people about the importance of the existence of lontar manuscripts.